ChemInform Abstract: Nanoconfined Light Metal Hydrides for Reversible Hydrogen Storage. Issue 16 (22nd April 2014) - de Jongh, Petra E.; Allendorf, Mark; Vajo, John J.; Zlotea, Claudia
Abstract Review: 58 refs.